KEASLIAN: DAYA TARIK WISATA BUDAYA DI MATA PEMUDA SUKU BADUY - Dhanik Puspita Sari; Jajang Gunawijaya; Nurbaeti (Bogor Hospitality Journal, 2023)
In cultural tourism, authenticity is one of the main elements that attract tourists to come and visit. The Baduy Luar tribe still holds firm to its culture and customs. However, it cannot be denied that the presence of social interaction between the Outer Baduy tribe and the tourists will cause a cultural shift, which in this case is acculturation that occurs among the youth of the Outer Baduy tribe. This research was conducted to find out the extent of the authenticity of the culture of the outer Baduy tribe and the preservation that will continue to be done by the youth of the outer Baduy tribe. The method used is a qualitative descriptive method with the leader of the Luar Baduy tribe (Jaro) and also the youth of the outer Baduy tribe. The results found that the youth of Baduy Luar have an understanding of the importance of cultural authenticity as an attraction for cultural tourism, they are also happy with the presence of tourists who come because it has an economic impact.